Implantes osseointegráveis na reabilitação dentária de pacientes irradiados em cabeça e pescoço: análise de sucesso e sobrevivência dos implantes a longo prazo - Condezo, Anthony Froy Benites (2016)
Advanced squamous cell cancers of the head and neck are commonly treated with a combination of modalities such as surgery, radiation, and/or chemotherapy. The result of this therapeuthic combination is maxillo-facial deformities that impair the function and aesthetics of these patients. The use of dental implants in irradiated patients is a challenging and demanding procedure in the rehabilitation of mastication, speech, aesthetics and recovery of quality of life. This study aims to evaluate the success rate and survival of dental implants in the rehabilitation of irradiated patients in head and neck region. A retrospective analysis of medical records of all patients undergoing the installation of dental implants for rehabilitation following radiation therapy for head and neck cancer at the Hospital Santa Catarina, São Paulo-SP, between the period 1995-2013. The study included only patients irradiated with a minimum total radiation dose of 50 Gy or greater and those receiving dental implants in the maxilla and mandible in the irradiated field of head and neck. The associations between survival of the implants and the clinical characteristics of patients and implants as well as radiotherapy were estimated by univariated Cox proportional hazards models. A total of 35 patients who had previously been irradiated in the head and neck had the installation of 169 dental implants in the maxilla and/or mandible during the analysis period. The estimated survival of the implants at 5 years was 91.5%. The survival rate at 5 years of implants placed in the maxilla was 92.4% and implants placed in the mandible was 90.9% (p = 0.808 ). The survival rate at 5 years of implants in patients treated with hyperbaric oxygen (HBO) adjuvant was 88.2 % and in patients not receiving HBO was 94.1% (p = 0.477). The survival rate at 5 years in women installed implants was 81.6% while in men was 98.9% (p <0.001). According to the type of radiotherapy, patients receiving intensity modulated radiotherapy (IMRT) or linear accelerator (AL) had implants survival rate at 5 years of 96.1% and 74.3%, respectively (p = 0.005). Osseointegrated implants are an alternative to dental rehabilitation for patients irradiated in the head and neck region. The survival rate of implants is significantly influenced by the patient's gender and the type of radiation used